If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 23 = 6x + 212 Reorder the terms: 23 + 13x = 6x + 212 Reorder the terms: 23 + 13x = 212 + 6x Solving 23 + 13x = 212 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 23 + 13x + -6x = 212 + 6x + -6x Combine like terms: 13x + -6x = 7x 23 + 7x = 212 + 6x + -6x Combine like terms: 6x + -6x = 0 23 + 7x = 212 + 0 23 + 7x = 212 Add '-23' to each side of the equation. 23 + -23 + 7x = 212 + -23 Combine like terms: 23 + -23 = 0 0 + 7x = 212 + -23 7x = 212 + -23 Combine like terms: 212 + -23 = 189 7x = 189 Divide each side by '7'. x = 27 Simplifying x = 27
| 6k^3-2k^2+15k-5=0 | | -3(9-x)=-36 | | 8x-2=-2 | | 8x=144 | | m^2-8m+4=-3 | | cos(x+2)sin(x)cos(x)=0 | | 5(7+x)=20 | | 5/46x+25/46=25/46 | | 1.5(10y+4)=17 | | 4=(m+2) | | 2cos^2(x)+3=5cos(x) | | 46r-38=62r-86 | | 2(2u-1)+4u=6(u-5)-2u | | 46r-38=63r-86 | | 5y+51=3(5y-3) | | sen(2x)+cosx=0 | | 5x+51=3(5y-3) | | 2cos^2x+3=5cosx | | 4=15+n | | 5v^2+10=510 | | 14-7w=-4 | | -4(x-1)+4=-3x+20 | | x^2=208 | | 62-2X=8X | | 16x+28=6x+298 | | -4(x-1)+4=3x+20 | | p^2+8=-17 | | -6b^2=-576 | | 8h-6(h+5)=4h | | -1+5x+6=6(x+3)-3 | | 5x+5x-1=-7(1-x) | | 5x+28=14x-44 |